An Innovative Approach to Pharmacy Law Education Utilizing a Mock Board of Pharmacy Meeting - D. Todd Bess; Jade Taylor; Carol A Schwab; Junling Wang; Jason A Carter (INNOVATIONS in Pharmacy, 2016)
A thorough understanding of pharmacy law by students is important in the molding of future pharmacy practitioners, but a standardized template for the best way to educate students in this area has not been created. A mock Board of Pharmacy meeting was designed and incorporated into the Pharmacy Law course at the University of Tennessee College of Pharmacy. Students acted as Board of Pharmacy members and utilized technology to decide outcomes of cases and requests addressed in a typical 2 day Tennessee Board of Pharmacy meeting. The actual responses to those cases, as well as similar cases and requests addressed over a 5 year period, were revealed to students after they made motions on mock scenarios. The mock Board of Pharmacy meeting engages the students in a way that lectures alone often fail to achieve with some initial evidence of successful student learning. Utilizing this teaching format as a law education tool challenges the status quo of pharmacy education and may serve as an impetus and catalyst for future innovations.